TRAINING DISCIPLINE AND RESPONSIBILITY: THE IMPLEMENTATION OF VALUES CLARIFICATION MODEL - Indah Mutiatul Karim; Ali Mustadi (JURNAL PENA SAINS, 2018)
The purpose of this study was to describe the influence of value clarification model to train discipline and responsibility for the student at PGRI University. This research is quasi-experiment. The population of this research is all students at the PGRI University. The sample of this research by using simple random sampling technique. The data were analyzed using MANOVA Test followed by Bonferroni post hoc test using SPSS 22.0 program. The results showed there is the influence value clarification model to build students’ attitude.